1997
DOI: 10.1063/1.120008
|View full text |Cite
|
Sign up to set email alerts
|

F induced layer disordering of GaAs/InGaP quantum wells

Abstract: F implantation (80–175 keV) induced GaAs/InGaP quantum well disordering was performed in a conventional furnace at 600–750 °C and in lamp annealing at 850 °C. Group V intermixing is found to be substantially enhanced for certain implantation and anneal conditions. Either the group III intermixing leading to lower band gaps or group V intermixing leading to higher band gaps may be made to dominate by choosing the process conditions. Only 50% reduction in integrated luminescence intensities from the as-grown lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The various grating parameters i.e., duty cycle, number of grating periods, and perturbation in refractive index are optimized for the single mode waveguide grating. The parameter values D o In-Ga = 61 × 10 −4 m 2 s −1 , D o P-As = 1.8 × 10 −7 m 2 s −1 (Das et al 1997) and E a In-Ga = 3.20 eV, E a P-As = 2.38 eV (Fancis et al 1993) has been assumed. An F-impurity concentration of 10 18 cm −3 suitable for a dose rate of 3 × 10 15 cm −2 at implantation energy ∼ 125 keV, has been used in this proposed structure for simulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The various grating parameters i.e., duty cycle, number of grating periods, and perturbation in refractive index are optimized for the single mode waveguide grating. The parameter values D o In-Ga = 61 × 10 −4 m 2 s −1 , D o P-As = 1.8 × 10 −7 m 2 s −1 (Das et al 1997) and E a In-Ga = 3.20 eV, E a P-As = 2.38 eV (Fancis et al 1993) has been assumed. An F-impurity concentration of 10 18 cm −3 suitable for a dose rate of 3 × 10 15 cm −2 at implantation energy ∼ 125 keV, has been used in this proposed structure for simulation.…”
Section: Resultsmentioning
confidence: 99%
“…F implanted waveguides on InP lattice matched quantum well are also discussed in (Bradshaw et al 1992). It has also been observed that detrimental implantation damage can be cured under pulse anneal conditions (Das et al 1997).…”
Section: Quantum Well Intermixingmentioning
confidence: 98%
“…A redshift was observed in an InGaAsP / InP QW structure by Zn diffusion, 7 and also in GaAs/ InGaP multiple QWs by thermal annealing 8 or fluorine implantation followed by annealing. 9 However, the k parameter, under the case of redshift, has never been reported.…”
mentioning
confidence: 99%
“…In recent years, great effort has been put in using DFQW as a tool. Last year, several remarkable papers have been published on advancing the intermixing process and technique [1][2][3][4][5][6][7][8][9][10][11][12][13]60]. The interdiffusion mechanism and determination of the diffusion rate as well as their understanding are also being studied [14][15][16][17][18][19][20][21].…”
Section: Ion Implantation A1gainpmentioning
confidence: 99%
“…F implantation induced Ga/InGaP QW disordering has been performed in conventional furnace and in lamp annealing enviroment [6]. Group-V intermixing is found to be substantially enhanced for certain implantation and annealing conditions.…”
Section: Ion Implantationmentioning
confidence: 99%